Combination of TiO2 nanoparticles and Echinometra mathaeis gonad extracts: In vitro and in vivo scolicidal activity against hydatid cysts. (November 2019) - Navvabi, Azita; Homaei, Ahmad; Khademvatan, Shahram; Khadem Ansari, Mohammad Hassan; Keshavarz, Mousa
Abstract: Echinococcosis (hydatid cyst) is a zoonotic disease in sheep, cattle, pigs, rats, and humans that is caused by larvae of the tapeworm Echinococcus granulosus . Several studies have shown that invertebrates exhibit activity against various parasites, but no studies are available of effects of extracts of the sea urchin Echinometra mathaei on hydatid cysts. Here, E . mathaeis gonad extracts were investigated for their effects on hydatid cysts, in the absence and presence of TiO2 nanoparticles. Different concentrations of E. mathaeis gonad extracts with and without TiO2 were applied for different times and the scolicidal activity of each of these conditions was determined on viable protoscolices. 15 μg/ml gonad extract + TiO2 was sufficient to kill 84% of the protoscolices after 60 min incubation. In vivo studies were performed on mice injected with E. granulosus protoscolices. Gonad extracts and gonad extracts combined with TiO2 were given by oral gavage for a period of 3 months. Combined application of extract and TiO2 increased the treatment efficiency, as shown by the reduction in number, size and volume of the cysts. Thus, sea urchin gonad extracts combined with TiO2 nanoparticles have anti-hydatic and scolicidal effects. Graphical abstract: Finding novel treatment options for hydatid cyst by evaluating whether the gonad from the Echinometra mathaei in combination with Tio2 exhibits activity against alive protoscoleces with comparison of the gonad extraction in vivo and in vitro . Image 1